Occurrence of biogenic amines in Thai soy sauces and soy bean pastes and their health concern - Deetae, P. (2019)
Biogenic amines (BAS) in 90 samples with different brands and formula of Thai fermented soy sauces (SS) and soy bean pastes (SBP) were analyzed by using HPLC after pre-column derivatization with dansyl chloride. Our results show that all SS and SBP samples contained BAS ranging from 2.10 to 594.60 ppm and from 3.21 to 82.18 ppm respectively. The type and the levels of BAS in the products varied depending on brands and formula. Of the 7 BAS studied, putrecine and cadaverine were the most common found (100% occurrence) in the SS samples followed by tyramine (93.33%) and histamine (86.67%). For SBP, occurrence of putrecine, cadaverine and spermidine (100%) were the most prevalent found in all samples, following by tyramine (85.71%). Our study revealed correlation between total BAS and some types of BAS including histamine putrecine and tyramine (p<0.01). The BAS levels in SS and SBP studied were mostly lower than the values considered harmful to consumer health.